An integrated framework for assessing coastal community vulnerability across cultures, oceans and scales. (21st April 2019) - Aswani, S.; Howard, J. A. E.; Gasalla, M. A.; Jennings, S.; Malherbe, W.; Martins, I. M.; Salim, S. S.; Van Putten, I. E.; Swathilekshmi, P. S.; Narayanakumar, R.; Watmough, G. R.
Abstract : Coastal communities are some of the most at-risk populations with respect to climate change impacts. It is therefore important to determine the vulnerability of such communities to co-develop viable adaptation options. Global efforts to address this issue include international scientific projects, such as Global Learning for Local Solutions (GULLS), which focuses on five fast warming regions of the southern hemisphere and aims to provide an understanding of the local scale processes influencing community vulnerability that can then be up-scaled to regional, country and global levels. This paper describes the development of a new social and ecological vulnerability framework which integrates exposure, sensitivity and adaptive capacity with the social livelihoods and food security approaches. It also measures community flexibility to understand better the adaptive capacity of different levels of community organization. The translation of the conceptual framework to an implementable method is described and its application in a number of "hotspot" countries, where ocean waters are warming faster than the rest of the world, is presented. Opportunities for cross-cultural comparisons to uncover similarities and differences in vulnerability and adaptation patterns among the study's coastal communities, which can provide accelerated learning mechanisms to other coastal regions, are highlighted. The social and ecological framework and the associated survey approach allow for future integration of local-level vulnerability data with ecological and oceanographic models.